Representing juvenile lifers: do attorneys in parole hearings matter? - Kokkalera, Stuti S. (Journal of crime and justice, 2022)
Courts and scholars have advocated for the right to legal representation in the parole process. The state examined in this study qualified that juvenile lifer parole candidates have the right to an attorney at their initial parole board hearing. Data drawn from written decisions issued by the state parole board were analyzed to determine the association between having an attorney and type of legal representation on two parole outcomes: (1) whether a candidate was granted or denied parole, and (2) length of interval terms, that is, number of years that a candidate waits for another hearing. While having an attorney at the hearing was not related to both outcomes, type of representation was associated with interval terms. Hearings with appointed (non-retained) attorneys were associated with reduced odds of a maximum interval term, while having retained attorneys was related to higher odds of a maximum interval term. Hence, state efforts to provide counsel are necessary since their presence is significantly associated with the ultimate time served by juvenile lifer candidates. Findings support the need for more comparative research across states as well as the inclusion of other parole-eligible populations.